The impact of stigmatization of psoriasis, atopic dermatitis and mastocytosis in different areas of life—A qualitative interview study. Issue 4 (29th July 2021) - Heim‐Ohmayer, P.; Freiberger, A.; Gedik, M.; Beckmann, J.; Ziehfreund, S.; Zink, A.; Hähl, W.; Schielein, M. C.
Abstract: Background: Stereotypes and false assumptions about chronic and visible skin diseases can determine the behaviour towards affected individuals and result in stigmatization or discrimination. Objective: The aim of this study was to analyze the perceived disease‐related stigmatization of individuals with psoriasis, atopic dermatitis (AD) or mastocytosis. The study also aims to broaden people‐centred knowledge of the effects of stigmatization in different areas of life, namely in everyday life, at work, in sports and in relationships. Methods: Qualitative in‐depth semi‐structured interviews were conducted among individuals with either psoriasis, AD or mastocytosis. Participants were recruited via self‐help networks and were asked to express their experience of stigmatization in different areas of life. All interviews were audio recorded, transcribed verbatim and evaluated based on Mayring's content analysis. Results: In total, 24 individuals aged 19–79 years and living in Germany were included in the study—eight for each disease. Stigmatization was experienced in all three diseases in all mentioned areas of life as well as in interaction with medical professionals. Self‐exclusion, negative self‐perception and negative behaviour of others were the most frequent experiences with stigmatization. Conclusion: Stigmatization, both internal and external, is an important factor contributing to the mental burden of people with chronic skin diseases. More research is needed to gain deeper insight into stigmatization and its psychological burden in various contexts to enhance people‐centred care in chronic skin diseases. Abstract :